A process plant retrofitting framework in Industry 4.0 perspective ⁎This research was funded by INAIL (Istituto Nazionale per l'Assicurazione Contro gli Infortuni sul Lavoro), the Italian National Institute for Insurance against Accidents at Work grant number BRIC 2018 project titled "Sviluppo di soluzioni smart attraverso metodologie Digital Twin per aumentare la sicurezza degli operatori durante i processi di manutenzione degli impianti produttivi"—BRIC ID12. Issue 1 (2021) - Carlo, Fabio Di; Mazzuto, Giovanni; Bevilacqua, Maurizio; Ciarapica, Filippo Emanuele; Ortenzi, Marco; Donato, Luciano Di; Ferraro, Alessandra; Pirozzi, Marco
Abstract: Retrofitting old plants is an excellent alternative to their replacement to prepare them for industry 4.0. Many papers are related to retrofitting, but few studies concerned the process industries. A framework to retrofit a process plant is presented and applied to a two-phase mixing plant providing a guide starting from the plant study and ending with the I4.0 paradigm implementation. The approach allowed to improve plant safety and maintainability conditions. The several issues arising during the retrofitting can be related to its multidisciplinarity aspects, the recursion in the definition of new variables to be monitored, and the information flow management.